Les régimes de retraite et les législations s’y rapportant - Le Houillier, Marcel (Assurances, 1983)
Mr. Marcel Le Houillier discusses retirement programs and the applicable legislation. The article is of particular interest as it is possible that there will be a reform of the large number of laws governing group retirement plans in Canada. The author describes current programs and legislation.